THE INFLUENCE OF AUGMENTED REALITY MEDIA TO IMPROVE UNDERSTANDING CONCEPTS IN SOCIAL STUDIES LEARNING IN ELEMENTARY SCHOOLS - Nur Fajrina; Ahmad Arifuddin; Heru Mudiyanto (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2025)
This research aims to determine the effect of using augmented reality media on increasing understanding of social studies learning concepts in elementary schools. This research is a quantitative research with a quasi-experimental design, namely a type of non equivalent control group design. The data collection techniques used are observation techniques, tests and questionnaires. Meanwhile, the sampling technique used saturated sampling with a sample size of 58 students. In addition, the data used in the research were analyzed using observation and questionnaire data analysis test, the N-Gain test, and the non-parametric hypothesis test, namely the Mann Whitney U test. The results of non-parametric hypothesis testing with the Mann Whitney U test, it shows that the significance value of 0.032 is smaller than 0.05, so Ha is rejected and H0 is accepted. This means that there is a significant influence between the use of augmented reality media on increasing understanding of social studies learning concepts in elementary schools.